1988
DOI: 10.1111/j.1439-0310.1988.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Homing in Harvester Termites: Evidence of Magnetic Orientation

Abstract: Colonies of Trinervitermes geminatus (Wasman) build a network of forked foraging trails. Homing workers choose, with few exceptions, those tracks at the forks of the pheromone trail network that lead direct to the nest. Assessments show that these workers are also able to distinguish between the homeward and outward direction along an unbranched trail. Experiments involving the alteration of the local natural magnetic field by means of a weak permanent magnet provide evidence that the termites recognise the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…To simulate the highly branched trail pheromone conditions within a termite nest, filter paper impregnated with 8 equal doses, with 10-cm-long pheromone trails (DTE (1 pg/cm) for R. chinensis and DDE (0.1 pg/cm) for O. formosanus, was used as the open arena in the dish-like cylinder arena as described above. The trails were spread out radially from the center of the circular device 20 . The device was placed in the center of the Helmholtz coil system for video recording as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate the highly branched trail pheromone conditions within a termite nest, filter paper impregnated with 8 equal doses, with 10-cm-long pheromone trails (DTE (1 pg/cm) for R. chinensis and DDE (0.1 pg/cm) for O. formosanus, was used as the open arena in the dish-like cylinder arena as described above. The trails were spread out radially from the center of the circular device 20 . The device was placed in the center of the Helmholtz coil system for video recording as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Volatile trail pheromones are not a reliable cue for positioning, so termites may use other cues for orientation. Thirty years ago, a simple test showed that the homeward direction was affected by the artificial magnetic field (AMF) in the termite Trinermtermes geminatus (Wasman) 20 . Because of technical restrictions, this previous study only used the distribution of termite numbers to describe magnetic orientation in termites.…”
mentioning
confidence: 99%
“…Bakers and Mather 1982 ) in termites (e.g. Rickli and Leuthold 1988 ; Jacklyn 1992 ), Monarch butterflies, Danaus plexippus (Guerra et al 2014 ), and recently also in the desert ant Cataglyphis (Formicidae) (Fleischmann et al 2018 ), to name just a few. The functional properties of the magnetic compass in arthropods have been analyzed in very few species only, and here, too, the findings do not indicate a uniform mechanism: Spiny lobsters appear to have a polarity compass (Lohmann et al 1995 ), while the beetle Tenebrio is reported to have an inclination compass (Vacha et al 2008 ).…”
Section: The Magnetic Compass and Its Use In The Animal Kingdommentioning
confidence: 99%
“…terrestrial species, aquatic and airborne species use information from the earth's magnetic field in variable environments. In case of terrestrial animals, magnetic field detection was shown for example in mealworm beetles Tenebrio molitor (Vácha and Soukopova 2004), honeybee Apis mellifera Bitterman 1985, 1989), fruit fly Drosophila melanogaster (Dommer et al 2008), harvester termites Trinervitermes geminatus (Rickli and Leuthold 1988) and cockroaches Periplaneta americana (Vácha 2006;Vácha et al 2009). In mammals, magnetic field perception was shown for mole rats Fukomys anselli and Spalax ehrenbergi (Burda et al 1990; Kimchi et al 2004), laboratory mice (Muheim et al 2006) as well as cattle Bos primigeniu, deer Capreolus capreolus and Cervus celaphus (Begall et al 2008;Burda et al 2009), bat species Eptesicus fuscus (Holland et al 2006), Nyctalus plancyi (Wang et al 2007) and Myotis myotis (Holland et al 2010) and possibly foxes Vulpes vulpes (Cerveny et al 2011).…”
Section: Introductionmentioning
confidence: 97%